APPLICATION OF MICROFILTRATION AND ULTRAFILTRATION FOR REUSING TREATED WASTEWATER; AS A SOLUTION TO EASE IRAN’S WATER SHORTAGE PROBLEMS (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Water shortage is a big problem in the Middle East. This paper investigates the possibility of reusing municipal wastewater by membrane filtration for non-potable consumption. The wastewater used for tests in this study was secondary effluent discharged from the secondary sedimentation pond of Ekbatan wastewater treatment plant in Tehran. These tests on reusing wastewater involved four main processes. Results showed that the best process was that ozone injection before MF and UF with COD removal efficiency of approximately 78 percent. In this case, removal efficiency of turbidity and TSS were 100 percent; additionally, traces of total and fecal Coliforms were completely removed. In the membrane processes, removal efficiency of TKN was about 40 percent. The removal efficiency of TP in all processes was about 7 percent, while it increased to 14 percent in the hybrid treatment. It can be concluded that all of further purification processes failed to achieve total phosphorus (TP) standards and thus in order to eliminate TP and reach allowable level, further researches are needed.